2004
DOI: 10.1007/s00125-004-1348-0
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations of membrane potential and cytosolic Ca2+ concentration in SUR1−/− beta cells

Abstract: Aims/hypothesis. SUR1(ABCC8) −/− mice lacking functional K ATP channels are an appropriate model to test the significance of K ATP channels in beta-cell function. We examined how this gene deletion interferes with stimulus-secretion coupling. We tested the influence of metabolic inhibition and galanin, whose mode of action is controversial. Methods. Plasma membrane potential (Vm) and currents were measured with microelectrodes or the patch-clamp technique; cytosolic Ca 2+ concentrations ([Ca 2+ ] c ) and mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
57
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 53 publications
(63 reference statements)
12
57
0
1
Order By: Relevance
“…7). Conversely, Kir6.2 −/− or SUR1 −/− mice, which have maximal hyperexcitability, and high [Ca 2+ ] i even at low glucose concentration [14,42], would be positioned on the 'descending' limb (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…7). Conversely, Kir6.2 −/− or SUR1 −/− mice, which have maximal hyperexcitability, and high [Ca 2+ ] i even at low glucose concentration [14,42], would be positioned on the 'descending' limb (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of Sur1KO and Control Islets-After four days of culture in 10 mM glucose, acute stimulation with glucose induced smaller mitochondrial hyperpolarization and oxygen consumption in single islet cells and intact islets from Sur1KO than control mice (30,31). Although this could suggest that glucose metabolism is impaired in islets lacking K ATP channels, the activity of glucokinase and the expression of genes of major metabolic enzymes were normal, leading the authors to conclude that a defect in glucose catabolism is not likely the cause of the defect in glucose-stimulated insulin secretion (31).…”
Section: Discussionmentioning
confidence: 99%
“…3. In contrast to wild-type β cells, the application of sodium azide did not result in hyperpolarization of Sur1KO β cells but did reduce the amplitude of Ca 2+ -dependent action potentials by directly inhibiting Ca 2+ channels [44,45]. Neither tolbutamide nor diazoxide had any effect on V m oscillations in K ATP null islets.…”
Section: Transgenic Mouse Modelsmentioning
confidence: 65%
“…The early electrophysiological studies done on isolated β cells from HI neonates using the patch clamp technique demonstrated a loss of K ATP channel activity and persistent Ca 2+ -dependent action potentials consistent with their excessive insulin release [47,73]. Similar analyses on isolated Sur1KO β cells identified a similar electrophysiological phenotype with loss of K ATP channels, persistent Ca 2+ -dependent action potentials, and elevated and slowly oscillating [Ca 2+ ] c , although in contrast to HI neonates, the knockout animals have normal blood sugar and insulin levels [44,133,137]. Later membrane potential measurements on Sur1KO β cells with intracellular microelectrodes revealed an oscillatory pattern ( Fig.…”
Section: Transgenic Mouse Modelsmentioning
confidence: 67%
See 1 more Smart Citation